2020
DOI: 10.1093/ibd/izaa252
|View full text |Cite
|
Sign up to set email alerts
|

Lower Rates of Colorectal Cancer in Patients With Inflammatory Bowel Disease Using Anti-TNF Therapy

Abstract: Background Chronic inflammation is a key factor for the development of colorectal cancer (CRC) among patients with inflammatory bowel disease (IBD). Despite the increased use of biologic agents in patients with IBD, their impact on colorectal carcinogenesis remains unclear. With the use of a large database, we sought to describe the effect of biologics on CRC among patients with IBD. Methods We evaluated a multicenter databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…In the 2000s, anti-tumor necrosis factor therapy for rheumatoid arthritis was linked to an increased risk for infection and malignancy (Bongartz et al, 2006). However, those findings have been contradicted by evidence from recent studies: Use of anti-tumor necrosis factor therapy after an initial cancer diagnosis does not influence recurrence or new cancer (Waljee et al, 2020), and patients with inflammatory bowel disease who are treated with this therapy have lower rates of colorectal cancer (Alkhayyat et al, 2020). These findings altogether merit further study of relationship between immunosuppression and the risk for cancer.…”
Section: The Advent Of Cancer Immunotherapy Highlights the Complex Relationship Between Autoimmunity And Cancermentioning
confidence: 99%
“…In the 2000s, anti-tumor necrosis factor therapy for rheumatoid arthritis was linked to an increased risk for infection and malignancy (Bongartz et al, 2006). However, those findings have been contradicted by evidence from recent studies: Use of anti-tumor necrosis factor therapy after an initial cancer diagnosis does not influence recurrence or new cancer (Waljee et al, 2020), and patients with inflammatory bowel disease who are treated with this therapy have lower rates of colorectal cancer (Alkhayyat et al, 2020). These findings altogether merit further study of relationship between immunosuppression and the risk for cancer.…”
Section: The Advent Of Cancer Immunotherapy Highlights the Complex Relationship Between Autoimmunity And Cancermentioning
confidence: 99%
“…In addition, SNOMED-CT allows for more concepts to be coded per clinical document compared to ICD making it more accurate in terms of documenting diagnoses and pertinent patient information. It is important to highlight that Explorys has been validated previously as a database (59) and in different specialties including gastroenterology (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)60,61).…”
Section: Discussionmentioning
confidence: 99%
“…To keep patients' information confidentiality, Explorys rounds cell counts to the nearest 10. Explorys database has been validated previously in multiple fields including surgery and gastroenterology (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Databasementioning
confidence: 99%
“…However, we believe that medication exposure in our study was a proxy for underlying chronic inflammation rather than AN progression occurring as a result of the medication exposure itself. Recent studies have suggested that immunomodulator 31 and anti-TNF exposure 32 may in fact be associated with lower cancer risk, but it is uncertain as to whether this is indirectly a result of achieving inflammatory control and mucosal healing or a direct chemoprotective effect. Further prospective data are required to understand the long-term impact of medical therapy, particularly biological drugs, on CRC risk in IBD.…”
Section: Discussionmentioning
confidence: 99%